2016
DOI: 10.1007/s10067-016-3330-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism and the risk of rheumatic autoimmune disease

Abstract: Testosterone deficiency has been linked with autoimmune disease and an increase in inflammatory markers, such as C-reactive protein (CRP), tumor necrosis factor, and interleukin-6 (IL-6). However, no large-scale longitudinal studies have examined this association. We examined whether untreated hypogonadism was associated with an increased risk of rheumatic autoimmune disease in a large nationally representative cohort. Using one of the nation’s largest commercial insurance databases, we conducted a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 24 publications
(24 reference statements)
1
34
0
4
Order By: Relevance
“…The pituitary–gonadal axis plays key roles in growth, sex development, metabolism, musculoskeletal build-up, strength, mood, energy, immune system, libido, and reproduction ( 22 24 ). Fluctuations in or impaired fine-tuning of the axis can result in a wide range of endocrine disorders that may be local but severe, e.g., infertility ( 25 ), or affect the entire body, as seen with adverse outcomes involving this axis such as sexual symptoms ( 4 ), depression ( 26 ), coronary heart disease/heart attack ( 27 ), autoimmune diseases such as arthritis ( 28 ), and diabetes ( 29 , 30 ). Testosterone forms a negative feedback loop that inhibits the production of both LH and gonadotropin-releasing hormone (GnRH) in the hypothalamus ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pituitary–gonadal axis plays key roles in growth, sex development, metabolism, musculoskeletal build-up, strength, mood, energy, immune system, libido, and reproduction ( 22 24 ). Fluctuations in or impaired fine-tuning of the axis can result in a wide range of endocrine disorders that may be local but severe, e.g., infertility ( 25 ), or affect the entire body, as seen with adverse outcomes involving this axis such as sexual symptoms ( 4 ), depression ( 26 ), coronary heart disease/heart attack ( 27 ), autoimmune diseases such as arthritis ( 28 ), and diabetes ( 29 , 30 ). Testosterone forms a negative feedback loop that inhibits the production of both LH and gonadotropin-releasing hormone (GnRH) in the hypothalamus ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both sex hormones and genes expressed on the X or Y chromosomes have been proposed to drive this bias, as exemplified by the fact that Klinefelter’s patients (XXY karyotype) express not only two X chromosomes but also reduced levels of androgens, and present with an increased risk for most of these disorders ( 114 ). Many patients of either sex with autoimmune disorders that predominantly affect women also demonstrated lower serum concentrations of androgens ( 76 , 115 , 116 ). Here, we will discuss the influence of androgens on the development and severity of RA, MS, and SLE.…”
Section: Androgens In Autoimmunitymentioning
confidence: 99%
“…A number of reports have suggested that androgens are protective in SLE. Although many male lupus patients have normal levels of androgens ( 194 ), men with hypogonadism are at increased risk of developing SLE ( 114 , 116 , 195 ) and testosterone supplementation of male lupus patients with genetic hypogonadism (Klinefelter’s syndrome) has, in two cases, been beneficial in treating lupus ( 196 , 197 ). However, no large-scale studies involving testosterone supplementation in male lupus patients have been reported ( 198 ).…”
Section: Androgens In Autoimmunitymentioning
confidence: 99%
“…Therefore, a lot of emphasis have been placed on the role of female sex hormones on immune responses and on different immune cell subsets, reviewed in 15 , 16 . Less is known about the impact of androgens on the immune system, but androgen deficiency in men is associated with increased risk for autoimmune disease 17 , 18 . In male mice, castration induces expansion of both the bone marrow and the splenic B-cell population 19 , 20 , which can be reversed by replacement with testosterone or dihydrotestosterone (DHT) 20 .…”
Section: Introductionmentioning
confidence: 99%